Guidelines for Purchase and Application of Poultry Manure for Organic Crop Production - James J. Ferguson; Michael R. Ziegler (EDIS)
Poultry manure and poultry litter (manure with bedding) is commonly used as a soil amendment and nutrient source for organic crop production. However, unless a farmer has an on-farm poultry facility, manure must be outsourced and delivered to the farm. Purchase, delivery, and application of these materials involve food safety, legal, regulatory, nutrient availability, and handling issues. Information on these topics can be found in Extension publications from university departments of agronomy, agricultural engineering, food science, horticulture, and poultry science. The purpose of this publication, however, is to integrate this information to provide guidelines and references for organic farmers who use outsourced poultry manure or litter in organic crop production. This document is HS973, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: April 2004.